Sintering of Fe-doped Bi0.5Na0.5TiO3 at < 1000 °C - Watcharapasorn A. (2014)
Fe-doped Bi0.5Na0.5TiO3 ceramics with Fe-ion content varied from 0 to 0.15 at.% were successfully prepared by conventional solid state reaction method. The sintering temperature used was between 850 and 1000 °C. X-ray diffraction patterns showed that all produced ceramics were single phase with a rhombohedral structure. SEM micrographs of the ceramics showed a dramatic change in densification behavior as a result of Fe-ion doping. At 850 °C, the undoped BNT ceramic had a very porous structure. As the Fe-ion concentration increased, the ceramics showed denser microstructures and, for the sample containing 0.15 at.% Fe, a very dense grain structure with almost no porosity was obtained. This microstructural observation agreed well with the measured density whose value increased with increasing Fe content. The relative density of at least 95% was achieved in 0.15 at.% Fe-doped BNT ceramics even when it was sintered at 850 °C. Increasing the sintering temperature only had an effect of increasing the grain size of this sample without appreciably affecting its density. The results of this investigation showed that addition of Fe2O3 in BNT could help improve the densification process and significantly reduced the sintering temperature of BNT ceramics. © 2006 Elsevier B.V. All rights reserved.